Impact of Releases from the Kef Eddir Dam on the Recharge of the Oued Damous Aquifer - HALLOUCHE, Ouassila; KADIR, Samra; BERKANE, Rabah; BOUKLACHI, Mohamed (GeoScience Engineering, 2023)
Artificial recharge is a good way to mobilize water in aquifers and recharge groundwater. Dam release is one of the techniques used for groundwater recharge. The periodic releases programmed by the Kef Eddir dam make it possible to recharge the Damous wadi aquifer located in the coastal wilaya of Tipaza in Algeria, whose overexploitation lowers the level of its water and causes a marine intrusion that pollutes it. In this work, to estimate the impact of these releases on aquifer recharge, we followed the releases of March 2020 and May 2021. The piezometric levels of groundwater were measured before the releases, during flow caused by them, and after them. These measures concern 13 wells located along the Damous wadi watercourse for the first year and 18 wells for the second year. These two years have seven wells in common. It allowed us to compare piezometric levels and recharges between 2020 and 2021. In the absence of releases on our return in May and June 2022, we measured the depth of water presence and took samples from 6 wells to measure the water conductivity. These measurements allow us to evaluate the piezometry of the water table over these three years, and the conductivity will indicate the degree of salinity of its water. Keywords: Artificial recharge; Kef Eddir dam; Oued Damous aquifer; Piezometric level; Releases.